Plasma cell tumors of the head and neck. Analysis of diagnostic difficulties based on literature and own data - F. Sh. Kamolova; L. Yu. Grivtsova; S. M. Samborskiy; V. B. Larionova; Yu. E. Ryabukhina; P. A. Zeynalova; A. M. Mudunov (Онкогематология)
Background. Extramedullary plasmacytoma (EP) of soft tissues, which in most cases affects the organs of the head and neck region, is a relatively rare malignant tumor. Until now, there are no consensus approaches to the diagnosis and treatment of EP. Differentiating EP from other types of non-Hodgkin’s lymphomas is difficult. There are difficulties in the differential diagnosis of EP and carcinomas in the head and neck region. Given the rare occurrence of this nosological form, the frequency of diagnostic errors is quite high, which dictates the need for a thorough description of each head and neck EP case.Objective of the study: analysis of possible difficulties and reasons for incorrect interpretation of diagnostic data, and treatment for head and neck EP.Materials and methods. Clinical and morphoimmunological data of 97 primary patients with B-cell non-Hodgkin’s lymphomas (B-NHLs) of the head-neck region were analyzed.Results. In our cohort we identified 2 tumor cases of a plasma cell nature, which amounted to 2 % among all B-NHLs. In one case, the process was located in the nasal cavity and clinically manifested itself with nosebleeds. The second case is a lesion of the mouth floor, primarily with the ulcer formation. In the first cases, at diagnosis, the immunohistochemistry (IHC) test was performed after patient’s chemotherapy and radiation treatment, which distorted the tumor immunophenotype. In the second cases with extensive process in maxillary sinuses, a complete and very detailed IHC test was carried out; however the data did not allow for a definitive diagnosis. Difficulties apparently arose in the interpretation of CD38 expression – main marker of plasmacytic line cells, as well as due to the unusual morphology.Conclusion. The described diagnostic situations dictate the need for a comprehensive algorithm in the diagnosis of head and neck tumors. It is advisable to perform an extended morpho-immunophenotypic study of the tumor (IHC, immunocytology, flow cytometry, etc.), if a tumor of a plasma cell nature is suspected, a morpho-immunological study of the bone marrow is indicated.